Routledge handbook of human rights in Asia - Gardiner, Christie M.; Varennes, Fernand de (Routledge Taylor & Francis Group, 2019)
"The Routledge Handbook of Human Rights in Asia provides a rich study of human rights challenges facing some of the most vulnerable people in Asia. While formal accession to core international human rights instruments is commonplace across the region, the realisation of human rights for many remains elusive as development pressure, violent conflict, limited political will and discrimination maintain human rights volatility across the region. This Handbook explores the underlying causes of human rights abuse in a range of contexts, considers lessons learnt from global, regional and domestic initiatives and provides recommendations and justifications for reform. Comprising 23 chapters, it examines the strengths and weaknesses of human rights institutions in Asia and covers issues including: - Participation, marginalisation, detention and exclusion - Private sector responsibility and security - Conflict and post-conflict rehabilitation - Trafficking, displacement and citizenship - Ageing populations, identity and sexuality. Drawing together a remarkable collection of leading and emerging scholars, advisers and practitioners, this Handbook is essential reading for students, scholars, policy makers and advocates of human rights in Asia and the world"--